Konsep Pendidikan Pluralis-Humanis Dalam Bingkai Pemikiran Gus Dur - Dwi Kurniawan (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2021)
Indonesia is a country with a very high level of national pluralism, the turmoil and conflicts that occur as a result of a shift in values ​​are very sensitive. This underlies that humanist pluralist education initiated by Abdurahaman Wahid to overcome the turmoil and conflicts that exist in society. For Gus Dur, pluralist education is a process of transferring knowledge that does not look at the background of students, which aims to make people devoted to their God. Meanwhile, humanist education is a process of guiding and directing students by looking at all the same and aiming at one. Thus humanist pluralist education is a process of transferring knowledge to guide and deliver humans to become whole, independent and free human beings and regardless of background and view all as the same.